Reading graphic design in cultural context - Maffei, Grace Lees-; Maffei, Nicolas P. (Bloomsbury Visual Arts, 2019)
"Reading Graphic Design in Cultural Context explains key ways of understanding and interpreting the graphic designs we see all around us, in advertising, branding, packaging and fashion. It situates these designs in their cultural and social contexts. Drawing examples from a range of design genres, leading design historians Grace Lees-Maffei and Nicolas P. Maffei explain theories of semiotics, postmodernism and globalization, and consider issues and debates within visual communication theory such as legibility, the relationship of word and image, gender and identity, and the impact of digital forms on design. Their discussion takes in well-known brands and everyday designed things including slogan t-shirts, car advertising, eBooks, corporate logos, posters and music packaging"--Back cover